Historical dictionary of socialism - Lamb, Peter (Historical dictionaries of religions, philosophies, and movements, 2016)
This third edition of Historical Dictionary of Socialism contains a chronology, an introduction, a glossary, and an extensive bibliography. This book is an excellent access point for students, researchers, and anyone wanting to know more about socialism.